2000
DOI: 10.21273/hortsci.35.3.480d
|View full text |Cite
|
Sign up to set email alerts
|

499 Postharvest Care and Handling Practices for Cut Poinsettia cv. `Winter Rose Dark Red'

Abstract: The traditional use of poinsettias has been as potted plants. A new poinsettia variety, `Winter Rose Dark Red', is performing well as a cut flower, lasting 2 to 3 weeks. Various postharvest handling procedures were examined, including stem processing methods at harvest, storage and transit conditions, as well as handling practices at the wholesale, retail, and consumer levels, to determine the best handling practices to maximize quality and longevity. At harvest, traditional latex controlling technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Floral solution heated to 38 or 100 °C (10 min) had no effect on vase life or days to fi rst cyathium abscission. Leonard et al (2000) also noted that 100 °C water dips had no effect. In contrast, a 24-h pulse of 10% sucrose reduced vase life and resulted in the earliest cyathium abscission (13.0 d).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Floral solution heated to 38 or 100 °C (10 min) had no effect on vase life or days to fi rst cyathium abscission. Leonard et al (2000) also noted that 100 °C water dips had no effect. In contrast, a 24-h pulse of 10% sucrose reduced vase life and resulted in the earliest cyathium abscission (13.0 d).…”
Section: Resultsmentioning
confidence: 93%
“…The stem ends of 'Renaissance Red' poinsettias were quite woody and produced little latex when harvested. Leonard et al (2000) concurred, noting that cut 'Winter Rose Dark Red' stems produced little latex and that 10-min 95% ethanol dips caused faster wilting. In contrast, Gordon et al (1986) found that 10-min dips in isopropyl alcohol applied immediately or within 1 h after harvest increased the time to 50% cyathium abscission in cut 'Annette Hegg Diva' and 'Annette Hegg Topwhite' poinsettias by 3 d. However, whereas Gordon et al (1986) defi ned vase life as days to 50% cyathium abscission, we differentiated between cyathium abscission and termination of vase life.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations